PERANAN DALEM WATURENGGONG DALAM PELAKSANAAN AJARAN AGAMA HINDU DI BALI - I Gusti Made Sunartha (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Brahmin theory dominates the analysis of Hinduism, so that it only gives birth to a philosophical mythological study of the existence of Hinduism in Bali. This study aims to analyze the role of Dalem Waturenggong (prime king with Balinese autonomy centralism in the Middle Bali era) in the implementation of Hindu religious teachings in Bali, which is also a form of analysis of Hinduism based on a theoretical perspective. Ksatria. The results in this study were collected using observation techniques, interviews and document studies, and analyzed using historical theory, phenomenology Edmund Hussrel, structuring Giddnes, dekonstruksi Jacques Derrida, structural functionalism and social systems. The results of this study indicate that the form of the role of Dalem Waturenggong in the implementation of Hindu religious teachings in Bali emphasizes the arrangement of Hindu teachings through theological paths. (Tattwa), sociological (politics, ethics, economics), and culture (customs, aesthetics). The main strategy applied by Dalem Waturenggong in managing the implementation of Hindu religious teachings in Bali is to carry out religious celebrations and historical celebrations. The implication of Dalem Waturenggong's role to the teachings of Hinduism in Bali is to ignite a good religious construction view from the community, so that it is firmly held by the Balinese people to this day, both theologically, politically and economically.